Comparative Efficiency of KOH-Activated Rice Husk Carbon in Adsorbing Pollutants from Laundry and Tofu Wastewater - Daning Kinanti Sutama; Dwi Indah Lestari; Erina Endah Kusuma Wardani; Shaddiqah Munawaroh Fauziah; Aulia Firda Alfiana (Science Education and Application Journal, 2025)
Comparative Efficiency of KOH-Activated Rice Husk Carbon in Adsorbing Pollutants from Laundry and Tofu Wastewater. This study aims to compare the adsorption capacity of rice husk-based activated carbon in overcoming pollution from two types of liquid waste, namely laundry waste and tofu liquid waste. The raw material of rice husk is processed through a carbonization process and chemical activation using potassium hydroxide (KOH), then used in a batch adsorption test. The parameters analyzed include Chemical Oxygen Demand (COD), Total Dissolved Solids (TDS), and Total Suspended Solids (TSS). The results show that the adsorbent material produced is able to reduce pollutant levels significantly. COD and TDS are more effectively reduced in laundry waste because the organic content and surfactants are more easily adsorbed, while TSS experiences a greater decrease in tofu waste due to the high suspended solids content. The adsorption process follows the Langmuir isotherm model with the regression values for both laundry and tofu wastewater of  R2>0.9, which indicates the occurrence of monolayer adsorption on the surface. This biosorbent has proven to be economical, environmentally friendly, and has the potential to be applied on a small scale, especially for household industries such as laundry businesses and tofu production. In addition to being relevant for local contexts, this approach can also be adopted globally in areas with high rice husk availability and similar waste management problems.